2022
DOI: 10.3847/1538-4357/ac5f3d
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Feedback from Narrow Line Region Outflows in Nearby Active Galaxies. IV. The Effects of Different Density Estimates on the Ionized Gas Masses and Outflow Rates

Abstract: Active galactic nuclei (AGN) can launch outflows of ionized gas that may influence galaxy evolution, and quantifying their full impact requires spatially resolved measurements of the gas masses, velocities, and radial extents. We previously reported these quantities for the ionized narrow-line region outflows in six low-redshift AGN, where the gas velocities and extents were determined from Hubble Space Telescope long-slit spectroscopy. However, calculating the gas masses required multicomponent photoionizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 77 publications
4
20
0
Order By: Relevance
“…The same applies regarding the use of [S II] as an electron density estimator (Baron & Netzer 2019;Davies et al 2020;Riffel 2021;Revalski et al 2022).…”
Section: Mass-outflow Rates and Energeticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same applies regarding the use of [S II] as an electron density estimator (Baron & Netzer 2019;Davies et al 2020;Riffel 2021;Revalski et al 2022).…”
Section: Mass-outflow Rates and Energeticsmentioning
confidence: 99%
“…Baron & Netzer (2019) suggest that the [S II] emission mainly arises close behind the ionization front, where most of the gas is neutral and n e is effectively lower (see also Figure 10 of Davies et al 2020). The bulk of the ionized gas is poorly traced by [S II], and using this line doublet as an electron density tracer may overestimate M out  (Revalski et al 2022). This systematic uncertainty would also affect the mass-outflow rates presented by Fiore et al (2017) and shown in Figure 10.…”
Section: Mass-outflow Rates and Energeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear sphere of an AGN has a complex gas environment (e.g., Revalski et al 2022). We examine here how the gas environment affects the radiation behavior of an IKN.…”
Section: The Influence Of Gas Density In a Nuclear Spherementioning
confidence: 99%
“…The nuclear sphere of AGN has a complex gas environment (e.g., Revalski et al 2022). We examine here how the gas environment affects the radiation behavior of an IKN.…”
Section: The Influence Of Gas Density In a Nuclear Spherementioning
confidence: 99%